Avaliação da qualidade e legibilidade das informações disponíveis na internet sobre tratamento das disfunções sexuais femininas - Mariza Miranda Abi-Ackel (2022)
Rationale and objectives: Approximately 40% of women will experience sexual dysfunction in their lifetime. The objective of this study was to assess the quality and readability of information available on the Internet on treatments for female sexual dysfunction (FSD). Study design: This study included websites with information on the treatment of FSD written in English; the websites were searched on Google, Bing, and Yahoo search engines. The DISCERN questionnaire was used to assess the quality of information and general quality of each website, and the Flesch Kincaid - Reading Ease Scale (FRES) was used to analyze the degree of readability. Two independent researchers performed the DISCERN assessments using a checklist prepared by the authors. Websites were classified into three groups, including public and private health institutions, institutions from different areas and libraries, and scientific journals and encyclopedias, which were subsequently compared. Differences between the groups were verified using the one-way analysis of variance. The relationship between DISCERN domain scores and the FRES readability scores was assessed using Pearson’s correlation analysis. Results: The 300 sites retrieved, 81 were duplicates and 155 were rule out. A total of 64 websites were evaluated, with DISCERN scores ranging from 40 to 55 and the FRES scores from 24.9 to 47.7, indicating moderate quality of information on the treatment of FSD and low readability. The mean scores of domain reliability, quality of information on FSD treatment, and overall website quality showed no statistically significant differences among the three website groups, with a moderate level of reliability and quality of information on the treatment of FSD according to the DISCERN assessment (mean, 37.8 ± 10.8). The mean FRES score was 43.8 points (range, 19–76; SD, 14.5), indicating the low readability of most websites, regardless of the group. The degree of correlation between DISCERN and FRES scores was statistically significant (p < 0.05) but relatively weak (r < 0.40), demonstrating that the quality of the information assessed by the DISCERN questionnaire was not related to the readability measured by the FRES. Conclusion: The websites analyzed in this study, which had information on the treatment of FSD in English, presented moderate information quality and reliability and low readability. The information available on the Internet on the treatment of FSD should be improved, with the focus of reaching the lay public. Keywords: female sexual dysfunctions, Internet, women’s health, sexuality.